2011
DOI: 10.1080/02640414.2011.572992
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different initial restrictive pressures used to reduce blood flow and thigh composition on tissue oxygenation of the quadriceps

Abstract: Blood flow restriction training technique can be affected by several factors resulting in changes in responses to training; therefore it is necessary to investigate and reveal detailed information about this novel training technique. Participants had their thigh size, thickness of subcutaneous fat, and regional bone free muscle mass measured prior to testing. A Near-Infrared Spectrometer was used to measure tissue oxygenation and a cardiovascular profiling system was utilised to measure stroke volume and heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…It is often speculated in the literature that thigh circumference or composition of the limb may restrict flow differently between individuals which might account for some of the variability in the response to low-load BFR exercise (Karabulut et al 2011b; Loenneke et al 2011e). For this analysis we included one model with thigh circumference and another using mCSA/fCSA to determine whether leg size or leg composition independently affected arterial blood flow restriction using either wide or narrow restriction cuffs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often speculated in the literature that thigh circumference or composition of the limb may restrict flow differently between individuals which might account for some of the variability in the response to low-load BFR exercise (Karabulut et al 2011b; Loenneke et al 2011e). For this analysis we included one model with thigh circumference and another using mCSA/fCSA to determine whether leg size or leg composition independently affected arterial blood flow restriction using either wide or narrow restriction cuffs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although recent manuscripts have postulated thigh circumference (Loenneke et al 2011e; Manini et al 2011) and limb composition (Karabulut et al 2011b) as overall determinants of arterial occlusion, this is the first investigation to date with a substantial subject pool of men and women to quantify the impact of leg size, leg composition, and brachial and ankle BP. Measurements were taken in the supine position, a position that has been used in studies investigating the clinical application of BFR (Kubota et al 2008, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that this difference in material may result in differences in in the ability to restrict blood flow and some of this difference may be due to differences in initial pressure. The initial pressure represents the pressure applied to the limb by the elastic cuffs prior to actual inflation (Karabulut et al, 2011). Although not always reported in the literature, it is important to set an appropriate initial pressure prior to inflating the elastic cuffs to the target pressure with the Kaatsu Master/Mini apparatus (Sato Sports Plaza, Tokyo, Japan).…”
Section: Possible Differences Between Cuff Materialsmentioning
confidence: 99%
“…In addition, a study conducted by Fahs et al (2011) showed that low-intensity knee extension exercise with BFR acutely increased arterial elasticity at the radial artery. As BFR reduces venous return and results in blood pooling in the vascular beds of the restricted limbs (Iida et al, 2005;Karabulut et al, 2011), it is likely that changing the cuff pressures used during BFR training and/or combining BFR exercises with different training protocols may affect the level of changes in both large and small arterial elasticity. All three conditions resulted in similar acute increases in large arterial elasticity, but the highintensity knee extension exercise session caused greater increases in small arterial elasticity compared with the lowintensity knee extension exercise and low-intensity knee extension exercise with BFR sessions.…”
Section: Introductionmentioning
confidence: 99%